Polarization and phase-shifting interferometry for arbitrary, locally varying polarization states - Rothau, Sergej; Kellermann, Christine; Mayer, Simon; Mantel, Klaus Peter; Lindlein, Norbert (Applied Optics, 2017)
This publication presents what we believe is a novel interferometric method for the simultaneous measurement of the phase and state of polarization of a light wave with arbitrary polarization; in particular, it can be varying elliptical. The measurement strategy is based on variations of the reference wave, concerning phase and polarization and processing the interference patterns so obtained. With this method, which is very similar to classical phase-shifting interferometry, the general analysis of spatially variant states of polarization and their phase fronts can be done in one measurement cycle. Furthermore, the analysis of different optical elements regarding the impact on the polarization and phase of the incoming light can be realized. After the theoretical description of the method and the mathematical discussion of different algorithms, the realized measurement setup is presented. Afterward, the accuracy of the method is discussed.